Particulate Matter and Volatile Organic Compounds Emissions and Their Health Impact: Spotlight on Solid Fuel Combustion - Jian Sun; Meng Wang; Jie Tian (Toxics)
Solid fuel combustion, while a crucial source of energy in many regions around the world, remains one of the primary contributors to air pollution, with significant implications for human health [...]